Socially-Legal Conditionality of Criminal Law Prohibitions in the Field of State Registration of Civil Rights - P. A. Grigorev (Теоретическая и прикладная юриспруденция)
The article contains the research on social and legal foundations of criminal law prohibitions related to the field of state registration of corporate rights and real estate rights. A public wrongfulness of falsification of public registry is evaluated through analyzing blanket norms of criminal law and norms of sector-specific laws. The conclusion is made that nowadays a protection of order in the field of state registration of rights is provided by criminal law in conjunction with administrative and civil law.